1978
DOI: 10.1002/cne.901820307
|View full text |Cite
|
Sign up to set email alerts
|

The organization of monoamine‐containing neurons in the brain of the sunfish (Lepomis gibbosus) as revealed by fluorescence microscopy

Abstract: The morphological organization of the monoamine-containing neurons in the brain of the sunfish (Lepomis gibbosus) was studied by means of the Falck-Hillarp histofluorescence method. No attempt was made to distinguish between norepinephrine and dopamine, both primary catecholamines (CA) yielding a similar yellow-green fluorescence after paraformaldehyde treatment. In the brain stem of this teleost fish, three groups of CA-containing neuronal somata have been found. First, there is a small collection of CA perik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…However, it is very difficult to generalize, as other cartilaginous fish such as Raja radiaia [33] show a considerable number of moderately stained dopaminergic neurons lying around the glomeruli, a situation strikingly similar to that found in amniotes. In teleosts, Parent et al [29] were unable to recognize any fluorescent perikarya but did report positive centrifugal fibers in the olfac tory bulb of the sunfish (Lepomis gibbosus) with the use of the Falck-Hillarp technique. More recently, Yoshida et al [30] and Nagatsu et al [28] have sug gested the presence of a population of TH-positive neurons, at present uncharacterized, in the olfactory bulb of the goldfish Carassius auralus.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is very difficult to generalize, as other cartilaginous fish such as Raja radiaia [33] show a considerable number of moderately stained dopaminergic neurons lying around the glomeruli, a situation strikingly similar to that found in amniotes. In teleosts, Parent et al [29] were unable to recognize any fluorescent perikarya but did report positive centrifugal fibers in the olfac tory bulb of the sunfish (Lepomis gibbosus) with the use of the Falck-Hillarp technique. More recently, Yoshida et al [30] and Nagatsu et al [28] have sug gested the presence of a population of TH-positive neurons, at present uncharacterized, in the olfactory bulb of the goldfish Carassius auralus.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies in Polypterus [Reiner and Northcutt, 1992] and teleosts [Sharma et al, 1989;Vecino et al, 1989;Batten et al, 1990] have described SP+ cell bodies and fibers in Vd except in the case of Apteronotus, where SP+ labeled neurons are localized in Vv [Weld and Maler, 1992]. Fibers positive for 5HT and TH and/or DA also characterize Vd [Parent et al, 1978;Parent and Northcutt, 1982;Yoshida et al, 1983;Hornby et al, 1987;Meek andJoosten, 1989, 1993;Roberts et al, 1989;Ekström et al, 1990;Hornby and Piekut, 1990;Johnston et al, 1990;Sas et al, 1990;Holmqvist and Ekström, 1991;Reiner and Northcutt, 1992;Manso et al, 1993;Anadón et al, 2002]. In most teleosts, TH-and DAimmunoreactive perikarya are found in similar patterns except in the case of Gnathonemus where differences have been reported Meek and Joosten, 1993].…”
Section: Comparisons With Other Actinopterygiansmentioning
confidence: 99%
“…Also, the deficit showed in both the acquisition and retention in avoidance behavior cannot be attributed to the lack of activity or initiative of the animal after lesion, because the level of escape is very high. In addition, the absence of effects on spatial memory or motor response (Portavella & Vargas, 2005) rules out a possible functional homology with the hippocampus and basal ganglia of tetrapods (Braford, 1995;Braford et al, 1992;Echteler & Saidel, 1981;Murakami et al, 1983;Nieuwenhuys & Verrijdt, 1983;Northcutt, 1995;Northcutt & Braford, 1980;Parent, 1986;Parent et al, 1978). Thus, we concluded that the lesion produced a deficit in the associative process between the discriminative stimulus and the shock (Portavella et al, 2002;2004a, 2004bPortavella & Vargas, 2005;Vargas et al, 2009).…”
Section: Function Of the Amygdala Homologous In Non Mammals Vertebratesmentioning
confidence: 65%
“…In actinopterygians, the telencephalon undergoes an eversion process that raises a serious difficulty in establishing homologies with the amygdala (Braford, 1995;Gage, 1983;Scalia & Ebbesson, 1971). However, the cytoarchitecture, the neurohistochemistry, studies of embryonic development, the pattern of connectivity and topological studies (Braford, 1995;Chanconie & Clairambault, 1975;Morgan, 1974aMorgan, , 1974bMurakami et al, 1983;Northcutt, 1981;Northcutt & Braford, 1980) suggest that the region Dmv of the teleost telencephalon is a good candidate to be considered the homologue of the pallial amygdala (Northcutt, 1995;Northcutt & Braford, 1980), although other authors suggest that Dmv could be homologous to the basal ganglia or the hippocampus of mammals (Murakami et al, 1983;Parent et al, 1978). Moreover, the pattern of connectivity, with strong sensory thalamic inputs and reciprocal connections with the hypothalamus, gives a distinctly limbic character to Dmv (Braford, 1995;Echteler & Saidel, 1981;Ito et al, 1986;Murakami et al, 1983;Striedter, 1991).…”
Section: The Amygdala Homologies Among Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation